Hamstring muscle architecture and myotonometer measurements in elite professional football players with a prior strained hamstring - Javier Núñez, F.; Martínez, J. C.; Overberg, J.-A.; Torreno, N.; Suarez-Arrones, L. (Biology of Sport, 2023)
The purpose of this study was to compare the fascicle length, angle pennation and mechanical properties of the biceps femoris long head (BFlh) in dominant and non-dominant limbs in previously injured and uninjured professional football players. Fifteen professional football players were recruited to participate in this study. Seven players had suffered a BFlh injury during the previous season. Myotonometry mechanical properties were measured in the proximal, common tendon and distal BFlh using MyotonPRO, and angle pennation and fascicle length were also measured. We observed significantly higher distal BFlh frequency, stiffness, decrement, relaxation and creep than in the common tendon and proximal BFlh. The previously injured players showed significantly higher frequency and stiffness, and lower relaxation and creep in the dominant BFlh than did uninjured players. There were no significant differences between the fascicle length and angle pennation in previously injured and uninjured BFlh. Myotonometric measurement provides a quick and inexpensive way to check the properties of the BFlh in professional football players. Professional football players with previous BFlh injury showed higher intrinsic tension and a poorer capacity to deform than did players with no injury to the BFlh.